PENGARUH PENUND AAN TAHAP PENUMPATAN DENGAN RESIN KOMPOSIT PADA TEKNIK SANDWICH TERHADAP KEKUATAN TARIK PELEKATAN SEMEN IONOMER KACA DAN RESIN KOMPOSIT - Yulita Kristanti; Diatri Nari Ratih (DiscoverSys Inc., 2002)
Sandwich technique, a combination filling technique using composite resin filling material and glass ionomer cement has been widely used. In fact, such a combination filling technique need Â ffcf i longer time compare to filling without combination. This research was done in order to know the influence of delayed fill ; ing in sandwich technique using composite resin related to the tensile strength between glass ionomer cement and composite resin.The materials studied consist of 16 samples, that were divided into 4 groups. The first one was used as the control groupt without delaying), while group II-IVwas used as the treating groups. Each group consist of 4 samples. The difference treatment between group II-IVwas the soaking time in the artificial saliva. Group II was soaked into artificial saliva (pH5)for 1 day, group , HI for 7 days, and group IVfor 14 days. The result of this research shows that the diference among the groups involved were very significant, except between group I and group II.The longer the sample was soaked into the artificial saliva, the tensile strength tends to decrease.